2017
DOI: 10.3390/educsci7030069
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Education: Reflecting on Application of Environmental Attitudes Measuring Scale in Higher Education Students

Abstract: Abstract:The Ecocentric and Anthropocentric Attitudes toward the Sustainable Development (EAATSD) scale measures environmental concern in relation to sustainable development. This article will discuss how this scale was tested with three groups of Dutch higher education students. Findings demonstrate that anthropocentric and ecocentric values are independent of the students' chosen course of study, suggesting that students attracted by the 'sustainable development' course title do not necessarily associate 'su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 121 publications
(111 reference statements)
1
13
0
3
Order By: Relevance
“…Furthermore, there are existing findings that support the importance of these three factors. Kopnina and Cocis [44] showed that the "choice of environmental issues" conducted by learners does not necessarily agree with the "purpose consciousness of environmental conservation". Compared with the results of this study, learners' choice of issues may occur not only in "Environmental Recognition/Conservation Responsibility Orientation" but also in "Thought Expansion/Fulfillment Orientation" as the stage of finding significance and in "Experience-Based Physical Activity Orientation" as the stage of formally understanding it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there are existing findings that support the importance of these three factors. Kopnina and Cocis [44] showed that the "choice of environmental issues" conducted by learners does not necessarily agree with the "purpose consciousness of environmental conservation". Compared with the results of this study, learners' choice of issues may occur not only in "Environmental Recognition/Conservation Responsibility Orientation" but also in "Thought Expansion/Fulfillment Orientation" as the stage of finding significance and in "Experience-Based Physical Activity Orientation" as the stage of formally understanding it.…”
Section: Discussionmentioning
confidence: 99%
“…By confirming the respective degrees of "Environmental Recognition/Conservation Responsibility Orientation", "Thought Expansion/Fulfillment Orientation", and "Experience-Based Physical Activity Orientation", we can confirm which stage of learning-in, about, or for the environment-the learner is in. For example, when a learner's motivation for environmental learning cannot be judged only by environmental conservation consciousness [44], the knowledge provided by this scale can offer a more detailed understanding of the learner's motivation. Through such detailed surveys, if learners have only reached the about stage, the scale may be used as material to devise learning measures related to "learning for the environment".…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that the research in recent years is aimed at the knowledge and perceptions of children and young people regarding the environment [62][63][64][65][66][67][68][69]. Again, research has shown that environmental education has a positive effect on students' greater interest in their environment [70][71][72].…”
Section: Significance and Aim Of The Studymentioning
confidence: 99%
“…Sin embargo, para el autor, la trascendencia involucra que se optimice la educación desde el medio ambiente; por otro lado, la educación tendrá un impacto mayor cuando los tres componentes se interrelacionen entre sí aportando un enfoque integral (Palmer, 1998;García y Muñoz, 2013). en ella se encuentran inmersos diferentes enfoques como la educación de la conservación, educación profunda, derechos animales, entre otros (Kopnina y Cocis, 2017). Los autores criticaron el enfoque inicial que se tomó en relación a la educación ambiental, debido a que las metas no se lograron al pasar los años.…”
Section: -346unclassified